"Normal Central Venous Pressure, " Significance of Reference Point and Normal Range. Issue 5663 (19th July 1969) - Debrunner, Felix; Bühler, Fritz
Abstract : The principal methods for determining the central venous pressure have been compared in 26 patients undergoing cardiac catheterization. The method in which the reference point is taken to be 10 cm. above the surface supporting a horizontal patient gave false high-pressure values. All the other methods, however, gave pressure values which corresponded to those obtained in the catheter studies.